Surgical Correction of Mandibular Prognathism - Ganguly, Brigadier Rasamay; Anand, Capt. S. C. (Indian Journal of Plastic Surgery, 1973)
1. The underlying skeletal defect and dental malocclusion in mandibular prognathism have been analysed.2. Various surgical procedures available for its correction have been reviewed.3. The advantage of osteotomy of ramus as compared to other procedures have been discussed.4. The operative technique of vertical osteotomy has been described in detail with clinical photographs.5. End results of vertical osteotomy being uniformly good the operation is recommended for wider use.